2021
DOI: 10.3892/etm.2021.10323
|View full text |Cite
|
Sign up to set email alerts
|

Insulin growth factor‑1 promotes the proliferation and osteogenic differentiation of bone marrow mesenchymal stem cells through the Wnt/β‑catenin pathway

Abstract: Bone marrow mesenchymal stem cells (BMSCs) are stem cells that exist in bone marrow tissue and have osteogenic differentiation potential. Insulin growth factor-1 (IGF-1) plays a key role in the proliferation and osteogenic differentiation of BMSCs. However, the specific mechanism of IGF-1 in cell proliferation and osteogenic differentiation remains unclear. In the present study, BMSCs were transfected with lentivirus carrying the siRNA-Wnt3a gene, and the Wnt3a level in BMSCs was revealed to be reduced by west… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…It is considered a cell adhesion protein, and osteoblasts cultured on a CTGF matrix exhibited enhanced bone nodule formation and matrix mineralization ( Hendesi et al, 2015 ). IGF1 is a multifunctional peptide growth factor that can induce strong proliferation and osteogenic differentiation in BMSCs ( Wu et al, 2020b ; Feng and Meng, 2021 ). During osteogenic differentiation, high expression of MMP13 in hMSCs grew on a type I collagen matrix.…”
Section: Discussionmentioning
confidence: 99%
“…It is considered a cell adhesion protein, and osteoblasts cultured on a CTGF matrix exhibited enhanced bone nodule formation and matrix mineralization ( Hendesi et al, 2015 ). IGF1 is a multifunctional peptide growth factor that can induce strong proliferation and osteogenic differentiation in BMSCs ( Wu et al, 2020b ; Feng and Meng, 2021 ). During osteogenic differentiation, high expression of MMP13 in hMSCs grew on a type I collagen matrix.…”
Section: Discussionmentioning
confidence: 99%
“…It had been shown to be more capable than BMP7 in inducing osteogenesis of BM-MSCs [ 50 ]. Furthermore, Feng and Meng [ 51 ] demonstrated that IGF1 promoted proliferation and osteogenesis in BM-MSCs via the Wnt/ β -catenin pathway.…”
Section: Discussionmentioning
confidence: 99%
“…IGF1 also promotes osteoblasts’ growth and apoptosis in vivo via the phosphoinositide 3-kinase (PI3K) pathway [ 21 ] . Additionally, IGF1 can induce strong proliferation and osteogenic differentiation in bone marrow mesenchymal stem cells via Wnt/β-catenin and Akt signaling pathways [ 22 , 23 ]. In 2017, Chen et al [ 24 ] performed a meta-analysis on the correlation between IGF1 and osteoporosis in a Chinese population and found that rs35767 in IGF1 was associated with risks of osteoporosis (OR = 1.31, 95% CI = 1.18–1.47, P value < 0.001), whereas other loci (e.g., rs2288377 and rs5742612) in IGF1 were not significantly correlated with osteoporosis.…”
Section: Discussionmentioning
confidence: 99%